2006
DOI: 10.1080/01448765.2006.9755026
|View full text |Cite
|
Sign up to set email alerts
|

Groundnut/Maize/Cassava Intercrop Yield Response to Fallow Age, Cropping Frequency and Crop Plant Density on an Ultisol in Southern Cameroon

Abstract: Two methods of intensifying crop production in 'no-external-input' slash and burn crop fallow rotation systems: increased crop density and increased cropping frequency, were tested on an Ultisol in southern Cameroon. Two common fallow types, secondary forest (forest fallow) and young volunteer regrowth dominated by Chmmolaena odomta (bush fallow) were cleared, bumed and planted to a groundnut/maize/cassava!plantain intercrop for one year or two consecutive years. Maize, cassava and plantain were planted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, higher plant density may be adopted with intercropping compared to sole cropping. A previous study on intercropping found that increasing maize plant density reduced legume grain yield and did not increase maize grain yield 43 . In the present study, D3 reduced intercropped pea grain yield compared with D1 and D2, consistent with the trend in biomass, but the increased grain yield of maize with increasing density compensated for the loss of grain yield of intercropped pea.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, higher plant density may be adopted with intercropping compared to sole cropping. A previous study on intercropping found that increasing maize plant density reduced legume grain yield and did not increase maize grain yield 43 . In the present study, D3 reduced intercropped pea grain yield compared with D1 and D2, consistent with the trend in biomass, but the increased grain yield of maize with increasing density compensated for the loss of grain yield of intercropped pea.…”
Section: Discussionmentioning
confidence: 85%
“…For farmers in the region, early maturing maize is the first food harvested from first season fields and it is the first marketable product for income generation. Maize density in intercrops is low because the main crop, groundnut, does not tolerate shading (Hauser et al, 2006b). In peri-urban areas, sole maize crops are rapidly gaining importance because growers have easy access to markets for maize sales and the purchase of fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Maize is grown as a minor component in the typical subsistence intercrop of groundnut/cassavalmaize (Hauser et al, 2006b) of the humid forest zone of West and Central Africa. However, farmers' interest in maize production is rapidly increasing because feed industries and breweries purchase dry maize grain in large quantities and the marketing of green cobs for fresh consumption is gaining importance, especially in urban and peri-urban areas.…”
Section: Introductionmentioning
confidence: 99%